2020
DOI: 10.1158/1055-9965.epi-19-0689
|View full text |Cite
|
Sign up to set email alerts
|

Adult Cancer Survivors' Engagement and Interest in Patient-Centered Research

Abstract: Background: Limited information is available about the representativeness of survivors engaging in patient-centered research, despite the potential for threats to generalizability. We thus aimed to assess the representativeness of survivors engaged or interested in research development.Methods: We used data from the Health Information National Trends Survey, a nationally representative survey, to identify survivors of adult cancers. Our outcomes of interest were based on responses to questions about engagement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Similar to trends in survivorship, clinical trials on survivorship have also increased during the past two decades [69][70][71][72][73]. Yet, only 5 percent of cancer survivors were engaged in these trials, although 26 percent of survivors reported willingness to be involved [70]. Most of these trials used a conventional approach, emphasizing investigator-identified priorities rather than a patientcentered approach [74,75].…”
Section: Survivorship and Health-related Quality Of Lifementioning
confidence: 99%
See 1 more Smart Citation
“…Similar to trends in survivorship, clinical trials on survivorship have also increased during the past two decades [69][70][71][72][73]. Yet, only 5 percent of cancer survivors were engaged in these trials, although 26 percent of survivors reported willingness to be involved [70]. Most of these trials used a conventional approach, emphasizing investigator-identified priorities rather than a patientcentered approach [74,75].…”
Section: Survivorship and Health-related Quality Of Lifementioning
confidence: 99%
“…This trend of improved survival is mainly due to advances in cancer diagnostic technology and therapeutics resulting from cancer science and trials [68]. Similar to trends in survivorship, clinical trials on survivorship have also increased during the past two decades [69][70][71][72][73]. Yet, only 5 percent of cancer survivors were engaged in these trials, although 26 percent of survivors reported willingness to be involved [70].…”
Section: Survivorship and Health-related Quality Of Lifementioning
confidence: 99%